How Non-Native English Speakers Perceive the Emotional Valence of Messages in Text-Based Computer-Mediated Communication. Issue 1 (2nd January 2019) - Hautasaari, Ari; Yamashita, Naomi; Gao, Ge
ABSTRACT: We explore how native and non-native English speakers interpret cues of emotional expression in native English speakers, text-only messages in two studies. In Experiment 1, 28 native English speakers and 28 Japanese non-native English speakers rated the emotional valence of 98 public Facebook status updates written by native English-speaking authors. We found that non-native speakers were less accurate at detecting the emotional valence and perceived messages more neutral or intensely negative than native speakers. In Experiment 2 we found that non-native speakers' cultural background and lack of confidence in second-language ability may influence how they adjust their perceptions on a message based on subsequent replies. Our results contribute to theoretical development in multilingual socioemotional communication in computer-mediated environments and have implications for design of technologies to support socioemotional text-based communication between native and non-native speakers.